Ex Situ Arterial Reconstruction During Normothermic Perfusion of the Liver. Issue 9 (September 2020) - Nasralla, David; Lembach, Hanns; Mergental, Hynek; Mirza, Darius; Friend, Peter; Muiesan, Paolo; Perera, MTPR
Abstract : Background: Aberrant hepatic arterial anatomy may be seen in up to 30% of liver grafts, and reconstruction prolongs the cold ischemic time or the arterialization times. If normothermic machine preservation (NMP) is used to preserve liver grafts, the presence of aberrant arterial anatomy poses a challenge. Dual arterial cannulation is a temporary solution to enable effective perfusion, until optimal circumstances are met for arterial reconstruction, without compromising ischemia time. To date the technical and logistical feasibility of arterial reconstruction ex situ and during NMP has not been reported. Methods: Series of 5 cases from the Consortium for Organ Preservation in Europe randomized controlled trial in which grafts with arterial anatomic variations were reconstructed while organs were perfused on NMP. Results: One donor after cardiac death and 4 donor after brain death livers with arterial anatomical variations reconstructed while on NMP were included. All patients survived transplantation, spending 1–7 d in intensive care unit and discharged home after 5–15 d. None of the cases developed early allograft dysfunction or any early technical complications. At follow-up, there were no late hepatic artery thrombosis, stenosis, or any other vascular–related complication. Four of 5 patients underwent magnetic resonance cholangiopancreatography at 6 mo with no evidence of ischemic cholangiopathy. Conclusions: The case series described above suggests that ex vivo arterial reconstruction surgery on liver grafts while on board the NMP device is feasible, safe, and effective.